Neutron-proton bremsstrahlung at 4.8 MeV - Whittaker, John (Department of Physics, 2016)
The differential cross-section for neutron-proton bremsstrahlung at an incident energy of 4.8 MeV has been measured where the outgoing nucleon angles were θₙ = 35°, θᵨ = 25°. An upper limit to d²σ/dΩₙdΩᵨ of 210 μb/sr² was found. The experimental method was unusual in that the target was an organic scintillation crystal which also served as recoil proton detector, and the bremsstrahlung photon was detected in addition to the two nucleons in a second crystal. An estimate of the cross-section corresponding to this experiment has been made using elastic scattering parameters. The measured upper limit is above this and other theoretical predictions, but represents a marked improvement over previous measurements in the energy range. Bibliography: p. 107-111.